Anaphylaxis following enteral exposure to Chlorella vulgaris. Issue 11 (2nd November 2020) - Abasszade, Joshua Haron; Rama Raj, Palaniraj; Tinson, Alistair John
Abstract : We present a case of a 75-year-old man who was admitted to an Australian tertiary emergency department with severe hypotension, wheeze, widespread urticarial rash and diarrhoea. On arrival to the emergency department following initial resuscitation by ambulance staff, he was admitted to the intensive care unit with a presumptive diagnosis of gastroenteritis. This diagnosis was later revised following the availability of tryptase levels and clarification of his presenting circumstances, which established a clear temporal relationship between his anaphylactoid symptoms and the oral ingestion of Chlorella vulgaris supplements. While there are a few case studies describing allergic/anaphylactic reactions to several other species of Chlorella, this appears to be the first reported case of anaphylaxis to C. vulgaris .